A Polite Foucault? Eighteenth-Century Politeness as a Disciplinary System and Practice of the Self. Issue 2 (October 2014) - Ylivuori, Soile
Abstract : Even though eighteenth-century politeness as a means of creating identity has recently been under much scholarly investigation, it has not been properly considered using theoretical approaches of identity and subjectivity as aids of analysis. This article examines politeness within two Foucauldian theoretical frameworks: as a disciplinary system and as an enabling practice of the self. The first approach sheds light on politeness as a kind of panopticon – an apparatus of power/knowledge, producing normative identity through constant surveillance. The second approach examines politeness from the individual's perspective, mapping out strategies of assuming and building polite subjectivity. My argument is that eighteenth-century politeness was not only a normalizing system of power, but also a practice of individuality and freedom. From this basis, I claim that a Foucauldian theoretical approach provides a fruitful new reading of politeness, opening up new areas of research.